2017
DOI: 10.1038/bjc.2017.149
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adiposity is an independent predictor of mortality in cancer patients

Abstract: Background:Prognostic significance of adiposity, at the time of cancer diagnosis, on survival is not clear. Body mass index (kg m−2) does not provide an appropriate assessment of body composition; therefore, the concept of the ‘obesity paradox’ needs to be investigated based on the prognostic significance of fat and muscle. Independent prognostic significance of adipose tissue in predicting mortality, importance of visceral and subcutaneous adiposity in the presence and absence of sarcopenia on survival, was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
158
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 36 publications
17
158
2
4
Order By: Relevance
“…In the early stage of colorectal cancer, the risk of death was lowest in the overweight patients (20). In different histopathological types of cancer, the risk of death decreased with increasing subcutaneous fat tissue (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the early stage of colorectal cancer, the risk of death was lowest in the overweight patients (20). In different histopathological types of cancer, the risk of death decreased with increasing subcutaneous fat tissue (21).…”
Section: Discussionmentioning
confidence: 95%
“…However, a favorable influence of overweight and obesity on the course of some neoplastic diseases have been also observed (17)(18)(19). Recently, a few studies have reported a relation between obesity and overweight and better prognosis in some cancer patients (20)(21)(22). In patients with locally advanced non-small-cell lung cancer obesity was associated with increased OS (22).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of either skeletal muscle or adipose tissue correlate with prognosis in cancer patients. Survival analysis in this study requires confirmation in a larger sample; however, we note with interest that the isolated loss of either fat or muscle was not associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…as <35.5 HU in men and <32.5 HU in women . Subcutaneous fat index was defined as ≥50.0 cm 2 /m 2 in men and ≥42.0 cm 2 /m 2 in women ( Table ).…”
Section: Methodsmentioning
confidence: 99%